Question
Solve for \( g \) \( 9=3(g+1) \) \( g=\square \) Submt
Ask by Parsons Bradley. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( g = 2 \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
The Deep Dive
To solve for \( g \), start by distributing the \( 3 \) on the right side of the equation: \[ 9 = 3g + 3. \] Next, subtract \( 3 \) from both sides: \[ 9 - 3 = 3g, \] which simplifies to: \[ 6 = 3g. \] Now, divide both sides by \( 3 \): \[ g = \frac{6}{3}, \] resulting in: \[ g = 2. \] So, \( g = 2 \).